2021
DOI: 10.3390/ijms22094542
|View full text |Cite
|
Sign up to set email alerts
|

NEIL1 and NEIL2 Are Recruited as Potential Backup for OGG1 upon OGG1 Depletion or Inhibition by TH5487

Abstract: DNA damage caused by reactive oxygen species may result in genetic mutations or cell death. Base excision repair (BER) is the major pathway that repairs DNA oxidative damage in order to maintain genomic integrity. In mammals, eleven DNA glycosylases have been reported to initiate BER, where each recognizes a few related DNA substrate lesions with some degree of overlapping specificity. 7,8-dihydro-8-oxoguanine (8-oxoG), one of the most abundant DNA oxidative lesions, is recognized and excised mainly by 8-oxogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Nevertheless, bearing in mind that knockout mice for Ape1 are embryonic lethal, the treatment with APE1 inhibitors might cause unforeseen on-target toxicities in normal tissues ( 14 ). On the contrary, the deficiency of individual DNA glycosylases, which initiate BER, is relatively well-tolerated, and therefore these enzymes may be more promising candidates for drug development ( 14 , 16 , 18 , 19 ). In particular, it has been described that the knockdown of OGG1 conferred sensitivity to PARP1 inhibition ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, bearing in mind that knockout mice for Ape1 are embryonic lethal, the treatment with APE1 inhibitors might cause unforeseen on-target toxicities in normal tissues ( 14 ). On the contrary, the deficiency of individual DNA glycosylases, which initiate BER, is relatively well-tolerated, and therefore these enzymes may be more promising candidates for drug development ( 14 , 16 , 18 , 19 ). In particular, it has been described that the knockdown of OGG1 conferred sensitivity to PARP1 inhibition ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…NTH1 and OGG1 are active only on double-stranded DNA, cleaving mainly oxidized pyrimidines and purines [ 15 , 21 , 22 ]. A study confirmed that 8-oxoG was mainly recognized and excised by OGG1, and when OGG1 was depleted or inhibited, NEIL1 and NEIL2 aggregated at sites of 8-oxoG damage as backup BER enzymes that complemented OGG1 [ 23 ]. NEIL1 and NEIL2 remove damaged bases from not only double-stranded DNA (dsDNA) and single-stranded DNA (ssDNA), but also remove 5-OHU damage in DNA bubbles [ 21 , 24 ].…”
Section: Dna Glycosylase Familymentioning
confidence: 97%
“…38 It was also reported that the upregulation of CCNB1 in primary liver cancer might be a potential biomarker to evaluate the prognosis of HCC. 39 In recent years, there was growing evidence suggesting that OGG1, in addition to DNA repair, played an epigenetic regulation role in transcription, 40 which could promote transcription of oncogene like c-Myc and inflammatory factors like CXCL1 and TNFα. 41,42 In summary, OGG1 was highly expressed in HCC patients and was related to the grading, staging, and prognosis of HCC, which could be used as a potential biomarker for HCC.…”
Section: F I G U R E 4 Protein-protein Interaction (Ppi) Network Of O...mentioning
confidence: 99%